(untitled) (Research, Society and Development, 2022)
Due to the low level of performance in mathematics of Brazilian students and their obsolete teaching, the need arises for pedagogical proposals that promote mathematical literacy. Possibilities for this are in the educational use of Information and Communication Technologies (ICT), with a fun and meaningful teaching. Besides, since 2018, the Curricular Common National Bases (CCNB) has been implemented, which guides directions of the use of ICT for teaching mathematics and discusses literacy topics. Because the CCNB is a subject of researches, the question is what these studies are about the guidelines of the base for the use of ICT to promote mathematical literacy? The investigation presents theoretical support in the ideas mathematical literacy of the CCNB and the possibilities of the using ICT to help the learning of mathematics. Methodologically, it is consists of bibliographical research, according to Lakatos and Marconi, with data extracted from articles available on academic Google, published between 2018 to 2021 and mapped by Textual Discursive Analysis, according to Moraes. The results show that use of technologies can be able to develop literacy skills like communication, representation, reasoning and solving mathematical problems. However, it was observed few theoretical works that relating the use of technologies and mathematical literacy, what could be an indication of gaps between the use of ICT and the development of pedagogical practices or the gap of teacher training for this purpose. For future works it´s suggested to investigate teacher training and experiences of use technologies to build mathematical literacy skills.